2012
DOI: 10.1002/lary.23365
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory identification testing as a predictor of the development of Alzheimer's dementia: A systematic review

Abstract: Although there is evidence suggesting an association between decreased olfaction and AD, rigorously designed longitudinal cohort studies are necessary to clarify the value of olfactory identification testing in predicting the onset of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 67 publications
1
75
0
Order By: Relevance
“…36,37 A 2012 systematic review identified 2 prospective, longitudinal studies that examined the utility of odor identification testing as a predictor of the development of AD, defined more rigorously with clinical criteria. 3,38,39 A recent analysis added substantively to this area, showing that baseline odor identification deficits were predictive of cognitive decline and transition to AD dementia in a large multiethnic population-based cohort of patients without dementia. 2 Our study, when continued longitudinally, offers the opportunity to test this hypothesis at an even earlier stage, with participants who do not have memory concerns or cognitive deficits.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 A 2012 systematic review identified 2 prospective, longitudinal studies that examined the utility of odor identification testing as a predictor of the development of AD, defined more rigorously with clinical criteria. 3,38,39 A recent analysis added substantively to this area, showing that baseline odor identification deficits were predictive of cognitive decline and transition to AD dementia in a large multiethnic population-based cohort of patients without dementia. 2 Our study, when continued longitudinally, offers the opportunity to test this hypothesis at an even earlier stage, with participants who do not have memory concerns or cognitive deficits.…”
Section: Resultsmentioning
confidence: 99%
“…These elements are also found throughout the olfactory nervous system in AD patients, justifying the early association between AD and olfactory loss [44]. Although some authors have found that even the OE in AD patients contains pathologically phosphorylated tau filaments [51], other authors have not been able to confirm this finding [52].…”
Section: Introductionmentioning
confidence: 95%
“…AD is a widespread disease and the most common cause of dementia among the elderly with an annual incidence of 1 % in persons aged 60-70 years and 6-8 % in those aged 85 years or more [44]. By age 65, the incidence of AD seems to double every 5 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory testing can, at least at the group level, reliably differentiate individuals with AD from normal controls [6,7]; olfaction declines during the evolution of AD [8]; and in longitudinal studies olfactory testing contributes to the prediction of who will later develop MCI or clinical AD [9-11, 12•, 13]. In 34 individuals cognitively intact prior to death, the extent of AD pathology at autopsy in central olfactory structures correlated significantly with the results on the Brief Smell Identification Test, a simple test of olfaction, suggesting that olfactory testing might help detect preclinical disease [14].…”
Section: Introductionmentioning
confidence: 99%